Patterns of spatial distribution and migration phenology of common pochards Aythya ferina in the Western Palearctic: a ring‐recoveries analysis. Issue 1 (11th September 2018) - Folliot, Benjamin; Guillemain, Matthieu; Champagnon, Jocelyn; Caizergues, Alain
Abstract : We used ringed‐recoveries to assess: 1) the connectivity (movements of individuals) between the three putative flyways (north–west Europe, central Europe, south–west Asia) of common pochards in the Western Palearctic, 2) possible spatio‐temporal variations in the distribution of the species, and, 3) temporal evolution in spring and autumn migration dates. Based on winter counts of common pochards in the north–west European flyway, we distinguished three periods in the analyses (1960–1990, 1991–2000 and 2001–2016), which correspond to successive periods of population increase, peak and decline, respectively. Whatever the season (wintering or breeding) and period of ringing, large probabilities of ring‐recoveries outside the flyway of origin (ringing) were recorded, suggesting a high connectivity between the three putative flyways. There was a significant trend towards an earlier departure from the wintering area, and an eastward shift of spring recoveries over periods. In contrast, neither autumn/winter recovery locations, nor departure dates from the breeding area in Latvia and Russia changed over periods. The latter results do not support the hypothesis that short‐stopping (i.e. a reduction of fall migration distances/delaying of departure dates from the breeding area) could explain the observed decline of wintering common pochards in the north–west European flyway. Indirect recoveries support that large proportions of individuals wintering in western Europe may originate from the south–west Asia flyway and more particularly from a region in Siberia located in the Ob river catchment area. Considering trends in numbers for the three flyways together confirmed the "vulnerable" IUCN status of common pochard in the Western Palearctic as a whole, with a 35% decline over the last decade. The important connectivity between the northwest, central European and southwest Asian flyways call for considering such conservation problems at a much broader scale than the regional flyway.